Trouble in Paradise: Problems in Academic Research Co-authoring. - Bozeman, Barry; Youtie, Jan (Science & Engineering Ethics, 2016)
Scholars and policy-makers have expressed concerns about the crediting of coauthors in research publications. Most such problems fall into one of two categories, excluding deserving contributors or including undeserving ones. But our research shows that there is no consensus on 'deserving' or on what type of contribution suffices for co-authorship award. Our study uses qualitative data, including interviews with 60 US academic science or engineering researchers in 14 disciplines in a set of geographically distributed research-intensive universities. We also employ data from 161 website posts provided by 93 study participants, again US academic scientists. We examine a variety of factors related to perceived unwarranted exclusion from co-author credit and unwarranted inclusion, providing an empirically-informed conceptual model to explain co-author crediting outcomes. Determinants of outcomes include characteristics of disciplines and fields, institutional work culture, power dynamics and team-specific norms and decision processes.